Observation of high partial-wave Feshbach resonances in 39K Bose–Einstein condensates - Yue Zhang; Liangchao Chen; Zekui Wang; Yazhou Wang; Pengjun Wang; Lianghui Huang; Zengming Meng; Ran Qi; Jing Zhang (New Journal of Physics)
We report the new observation of several high partial-wave (HPW) magnetic Feshbach resonances (FRs) in ^39 K atoms of the hyperfine substate $\left|F = 1,m_{F} = -1\right\rangle$ . These resonances locate at the region between two broad s -wave FRs from 32.6 G to 162.8 G, in which Bose–Einstein condensates can be produced with tunable positive scattering length obtained by magnetic FRs. These HPW FRs are induced by the dipolar spin–spin interaction with s -wave in the open channel and HPW in the closed channel. Therefore, these HPW FRs have distinct characteristics in temperature dependence and loss line shape from that induced by spin–exchange interaction with HPWs in both open and closed channels. Among these resonances, one d -wave and two g -wave FRs are confirmed by the multichannel quantum-defect theory calculation. The HPW FRs have significant applications in many-body physics dominated by HPW pairing.